Resiliensi Ditinjau Dari Gender Pada Anggota Resimen Mahasiswa Di Kota Bekasi : Azka Zine Zidane Firdaus, Lenny Utama Afriyenti, Rika Fitriyana - Zine Zidane Firdaus, Azka; Utama Afriyenti, Lenny; Fitriyana, Rika (Fakultas Psikologi Universitas Bhayangkara Jakarta Raya, 2024)
The objective of this research is to identify the differences in resilience based on gender among members of the Student Regiment in Bekasi City. The sampling technique used in this study is saturated sampling with a total of 70 respondents. The measurement instrument used is the Resilience Scale. The results of this research show that the mean resilience score for male members is 32.77, while for female members, it is 37.80. The results of the statistical test also indicate a significance level of 0.298 (p< 0.05), which means that there is no significant difference between the resilience of male and female members. As for suggestions that can be given to the Student Regiment members in Bekasi City, it is important to take care of and develop their resilience by creating good planning, maintaining self-motivation by always being enthusiastic to move forward, taking initiatives in facing all challenges, and exercising self-control by managing negative emotions that may lead to impulsive behavior. This will enable the Student Regiment members to direct their behavior towards more positive consequences and adopt a mindset that sees problems as learning experiences, making them more confident and prepared to go through the organizational process and face the dynamics within it.